The influence of employee satisfaction on turnover intention at private colleges in Kuantan: the moderating effects of social support / Normadiana A. Manan - A. Manan, Normadiana (2014)
The main objective of this study is to investigate the influence of employee satisfaction on turnover intention and to examine whether social support moderates the relationship between employee satisfaction and turnover intention. This study was conducted among academic staff at three private colleges in Kuantan, namely IKIP International College, Shahputra University College, and Cosmopoint University of Technology. The questionnaire was developed based on 5-point Likert scale and it was personally distributed and collected to the 200 academic staff at these three private colleges in Kuantan. However, only 147 questionnaires were collected and this equivalent to 73.5% of the respondents. The data collected for this study were analysed using Statistical Package for Social Sciences (SPSS), version 20. Pearson Correlation Coefficient and Multiple Regression were applied in analysing and interpreting the data. The result of employee satisfaction on turnover intention generally supports the hypothesis in this study. Pay is the strongest factor that supports the relationship between employee satisfaction and turnover intention. Another factors that contributed to the findings in this study were promotion, workload, and supervision need to be considered and attention by the management to retain the valuable employee in the organization. The results further indicate that social support has a significant but weak impact on employee satisfaction and turnover intention. Some of suggestions and recommendations were provided for future research and private colleges in order to produce more accurate and comprehensive results for upcoming research.